2007
DOI: 10.1007/s11064-007-9352-7
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Breakdown and Iron Changes in Huntington’s Disease: Pathogenesis and Treatment Implications

Abstract: The data suggest early in the HD process, myelin breakdown and changes in ferritin iron distribution underlie the pattern of regional toxicity observed in HD. Prospective studies are needed to verify myelin breakdown and increased iron levels are causal factors in HD pathogenesis. Tracking the effects of novel interventions that reduce myelin breakdown and iron accumulation in preclinical stages of HD could hasten the development of preventive treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
277
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(306 citation statements)
references
References 89 publications
27
277
1
1
Order By: Relevance
“…Abnormalities in WM microstructure have been reported in postmortem studies of humans with HD (de la Monte et al 1988;Halliday et al 1998). This research was confirmed by in vivo studies with magnetic resonance imaging (MRI), which reported extensive WM volume loss (Aylward et al 1998, 2012Thieben et al 2002;Rosas et al 2003;Fennema-Notestine et al 2004;Beglinger et al 2005;Ciarmiello et al 2006;Paulsen et al 2006;Jech et al 2007;Squitieri et al 2009;Tabrizi et al 2009Tabrizi et al , 2011Tabrizi et al , 2012Tabrizi et al , 2013) and changes in WM microstructure (Mascalchi et al 2004;Reading et al 2005;Rosas et al 2006;Bartzokis et al 2007;Sritharan et al 2010;Stoffers et al 2010;Dumas et al 2012;Matsui et al 2014). Nevertheless, these previous macro-and microstructural studies focused on wholebrain WM or Region of Interest analyses.…”
Section: Introductionmentioning
confidence: 81%
“…Abnormalities in WM microstructure have been reported in postmortem studies of humans with HD (de la Monte et al 1988;Halliday et al 1998). This research was confirmed by in vivo studies with magnetic resonance imaging (MRI), which reported extensive WM volume loss (Aylward et al 1998, 2012Thieben et al 2002;Rosas et al 2003;Fennema-Notestine et al 2004;Beglinger et al 2005;Ciarmiello et al 2006;Paulsen et al 2006;Jech et al 2007;Squitieri et al 2009;Tabrizi et al 2009Tabrizi et al , 2011Tabrizi et al , 2012Tabrizi et al , 2013) and changes in WM microstructure (Mascalchi et al 2004;Reading et al 2005;Rosas et al 2006;Bartzokis et al 2007;Sritharan et al 2010;Stoffers et al 2010;Dumas et al 2012;Matsui et al 2014). Nevertheless, these previous macro-and microstructural studies focused on wholebrain WM or Region of Interest analyses.…”
Section: Introductionmentioning
confidence: 81%
“…Since the majority of brain cholesterol is synthesised during prenatal life [45], HD neurodegeneration may be seeded early, with individuals only becoming symptomatic later in life. A current hypothesis suggests that errors in myelination during development may be a factor in human HD, taking many years to manifest before onset due to compensatory mechanisms that function early but become overwhelmed in the aged brain [46]. Alternatively, early changes to cholesterol biosynthesis may be independent of the pathological processes in this HD model.…”
Section: Discussionmentioning
confidence: 98%
“…Differentiating oligodendrocytes have very high iron requirements and may have a critical role in brain iron uptake (reviewed in Bartzokis et al, 2007a;Bartzokis et al, 2007b). This may be especially important in the hippocampus where 50% of oligodendrocytes are juxtaposed directly on blood vessels and may thus be in a position to acquire iron directly from the vasculature (Vinet et al, 2010).…”
Section: Discussionmentioning
confidence: 99%